Influence of HLA-G polymorphisms in human immunodeficiency virus infection and hepatitis C virus co-infection in Brazilian and Italian individuals. - da Silva, G K; Vianna, Priscila; Veit, Tiago Degani; Crovella, Sergio; Catamo, Eulalia; Cordero, Elvira Alicia Aparicio; Mattevi, Vanessa Suñé; Lazzaretti, Rosmeri Kuhmmer; Sprinz, Eduardo; Kuhmmer, Regina; Chies, José Artur Bogo (Infect Genet Evol, 2014)
OBJECTIVE: This study aimed to investigate the role of Human Leukocyte Antigen (HLA)-G in the susceptibility to HIV-1 infection through the analysis of the HLA-G 3' untranslated region (UTR) polymorphisms 14 bp insertion/deletion (rs66554220) and +3142C>G (rs1063320). DESIGN: We analyzed 582 HIV-1 infected patients and 626 uninfected individuals from Brazil and Italy in a case-control study. METHODS: HLA-G polymorphisms were genotyped using PCR, PCR-RFLP assays or direct sequencing. All analyses were stratified by ethnicity. Genotypic, allelic and diplotypic frequencies were compared between HIV-1 infected subjects and controls using Chi-square or Fischer exact tests. Also, haplotypic frequencies were estimated using MLocus software. RESULTS: African-derived HIV-infected individuals presented a higher frequency of the 14 bp insertion allele as compared to non-infected individuals (0.468 versus 0.373, respectively; p(Bonf) = 0.010). A higher frequency of the 14 bp insertion +3142G (insG) haplotype (0.456 versus 0.346, p<0.001) and the insG/insG diplotype (OR=1.88, 95%CI = 1.08-3.23, p=0.021) was observed among African-derived patients as compared to uninfected controls. Also, we observed a higher frequency of the ins/ins genotype among African-derived HIV patients co-infected with HCV (OR=2.78, 95%CI = 1.20-6.49, p = 0.008). CONCLUSIONS: Our data point out to an increased frequency of alleles and genotypes associated with low HLA-G expression among African-derived patients, suggesting a potential role for HLA-G in the susceptibility to HIV-1 infection and HCV co-infection in those individuals.
Keywords: 3' Untranslated Regions; Adolescent; Adult; African Continental Ancestry Group; Aged; Brazil; Coinfection; Gene Frequency; Genetic Variation; Haplotypes; Hepatitis C; HIV Infections; HLA-G Antigens; Humans; Italy; Male; Middle Aged; Polymorphism, Single Nucleotide; Young Adult